Does teaching audit improve standards, and affect MCQ results in undergraduate trauma and orthopaedic tuition? - Spencer, J. D. (Royal College of Surgeons of England, 1993)
Over the study period from 1981 to 1987 inclusive, student critiques were scored to indicate the undergraduates' perception of the quality of teaching they received on each 2-month attachment to the trauma and orthopaedic surgical departments of two teaching hospitals. The medical staff and the environment in the two teaching hospitals were different. It was found that while the mean MCQ results did not change significantly throughout the study period, an improvement was noticed in the perceived quality of undergraduate tuition, especially at one hospital.